2014
DOI: 10.1021/am4054332
|View full text |Cite
|
Sign up to set email alerts
|

Composition-Tuned ZnO/ZnxCd1–xTe Core/Shell Nanowires Array with Broad Spectral Absorption from UV to NIR for Hydrogen Generation

Abstract: For highly efficient photoelectrodes, the materials used must have both a broad absorption range and large separation efficiency of photogenerated electron-hole pairs. Type II heterostructures with a ternary shell meet these two requirements and thus are recognized as being an ideal materials system for application in photocatalytic hydrogen production. Here, a ZnO/ZnxCd1-xTe core/shell nanowires array with a broad absorption edge from UV (380 nm) to NIR (855 nm) was fabricated via a chemical vapor-deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Compared with the well-crystallinity of CdS NWs, the MoS 2 layer is polycrystalline although there are some crystalline domains with random lattice fringes. A closer examination of the interface between MoS 2 and CdS shows that the inconspicuous lattice fringes of MoS 2 directly connect to the continuous lattice fringes of CdS, which is expected to facilitate the separation and transfer of photogenerated charge carriers [27,31]. Further increasing molar ratio of MoS 2 loading to 20%, as shown in Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Compared with the well-crystallinity of CdS NWs, the MoS 2 layer is polycrystalline although there are some crystalline domains with random lattice fringes. A closer examination of the interface between MoS 2 and CdS shows that the inconspicuous lattice fringes of MoS 2 directly connect to the continuous lattice fringes of CdS, which is expected to facilitate the separation and transfer of photogenerated charge carriers [27,31]. Further increasing molar ratio of MoS 2 loading to 20%, as shown in Fig.…”
Section: Resultsmentioning
confidence: 84%
“…59 n-n type heterojunctions yield similar results. 35 In the case of photo- 17 due to shorter collection times. Light reflection increases the ratio of non-diffusive absorption and diffusive scattering, which results in a reduction in photon harvesting.…”
Section: -58mentioning
confidence: 99%
“…For example, Zn x Cd 1Àx Te in conjunction with ZnO in heterostructures helps to extend the absorption of solar energy into the NIR region, which can be as high as 22% of the solar spectrum. 35 In the process of fabrication, inorganic nanostructures are generally subjected to thermal treatment(s), note that there are exceptions. Various studies have shown the dependence of H 2 production on processing parameters, such as the calcination temperature.…”
mentioning
confidence: 99%
“…IIeVI group semiconductors (e.g., CdS, CdSe, ZnSe) have been widely chosen as sensitizer layer because of their appropriate optical properties, abundance, easy manufacture [26e29]. Compared with the most studied binary IIeVI semiconductors, ternary alloy semiconductor materials (e.g., ZnCdSe [25,30,31], ZnCdTe [32], CdSSe [33,34]) distinguish themselves by many advantages, such as the tunable band gaps [35,36], synergistic effects for the light harvesting [26,37] and higher chemical stability [38,39]. In 2013, Pan et al [39] studied the CdSe x Te 1Àx alloyed quantum dots (QD) sensitized solar cell (QDSSC) based on mesoporous TiO 2 film, and found that the CdSe x Te 1Àx QDs enormously broadened the light absorption of the QDSSC into near infrared range and the solar energy conversion efficiency reached above 6%.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Pan et al [39] studied the CdSe x Te 1Àx alloyed quantum dots (QD) sensitized solar cell (QDSSC) based on mesoporous TiO 2 film, and found that the CdSe x Te 1Àx QDs enormously broadened the light absorption of the QDSSC into near infrared range and the solar energy conversion efficiency reached above 6%. Recently, Zhan et al [32] synthesized a composition-tunable ternary alloy ZnO/ Zn x Cd 1Àx Te core/shell nanowire arrays which exhibited significantly enhanced PEC hydrogen generation activity. In the previous report of our group, we reported a TiO 2 /CdS x Se 1Àx (0 < x < 1) core/ shell NWAs photoelectrode and demonstrated that the alloying of CdS and CdSe on TiO 2 NWAs greatly improved the PEC hydrogen generation performance, especially in case of TiO 2 /CdS 0.52 Se 0.48 composite electrode, due to the enhanced light absorption and charge separation [40].…”
Section: Introductionmentioning
confidence: 99%